Given a positive sequence $(a_n)$. Prove that if $\displaystyle \sum_{n=1}^{\infty} a_n$ converges, then so does $\displaystyle \sum_{n=1}^{\infty} a_n^{\frac{n}{n+1}}$.

I tried to use the root test, and I was stuck with the case $\lim \sup \sqrt[n]{a_n}=1$. Maybe we need some trick here.

Thanks so much.


Let $b_n=a_n+e^{-n}$. The specific choice $e^{-n}$ here isn't too important, we just want to make sure that the $b_n$'s still converge but not too quickly. Now $\sum b_n$ converges and $b_n^{n/(n+1)}>a_n^{n/(n+1)}$, so if $\sum b_n^{n/(n+1)}$ converges then so does $\sum a_n^{n/(n+1)}$.

Now we can use the limit comparison test, in its one-directional form:

If $(a_n),(b_n)$ are positive sequences and $\liminf_{n\to\infty}\frac{a_n}{b_n}>0$, then if $(a_n)$ converges so does $(b_n)$.

$$\liminf_{n\to\infty}\frac{b_n}{b_n^{\frac n{n+1}}}=\liminf_{n\to\infty}b_n^{\frac 1{n+1}},$$ so taking a $\log$, we wish to show that $\liminf_{n\to\infty}\frac{\log(b_n)}{n+1}>-\infty.$ But

$$b_n>e^{-n}\implies \liminf_{n\to\infty}\frac{\log(b_n)}{n+1}>\liminf_{n\to\infty}\frac{-n}{n+1}=-1.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.